Toward a more humane genetics education: Learning about the social and quantitative complexities of human genetic variation research could reduce racial bias in adolescent and adult populations. Issue 3 (18th March 2019) - Donovan, Brian M.; Semmens, Rob; Keck, Phillip; Brimhall, Elizabeth; Busch, K. C.; Weindling, Monica; Duncan, Alex; Stuhlsatz, Molly; Bracey, Zoë Buck; Bloom, Mark; Kowalski, Susan; Salazar, Brae
Abstract: When people are exposed to information that leads them to overestimate the actual amount of genetic difference between racial groups, it can augment their racial biases. However, there is apparently no research that explores if the reverse is possible. Does teaching adolescents scientifically accurate information about genetic variation within and between US census races reduce their racial biases? We randomized 8 th and 9 th grade students ( n  = 166) into separate classrooms to learn for an entire week either about the topics of (a) human genetic variation or (b) climate variation. In a cross‐over randomized trial with clustering, we demonstrate that when students learn about genetic variation within and between racial groups it significantly changes their perceptions of human genetic variation, thereby causing a significant decrease in their scores on instruments assessing cognitive forms of prejudice. We then replicate these findings in two computer‐based randomized controlled trials, one with adults ( n  = 176) and another with biology students ( n  = 721, 9 th –12 th graders). These results indicate that teaching about human variation in the domain of genetics has potentially powerful effects on social cognition during adolescence. In turn, we argue that learning about the social and quantitative complexities of human genetic variation research could prepare students to become informed participants in a society where human genetics is invoked as a rationale in sociopolitical debates.